Study on the Influence of Excavation of Superlarge and Ultra-Deep Foundation Pits on the Pile Foundation of Existing Viaducts - Wancai Zhong; Nianyong Huang; Nan Nie; Haibin Ding; Feng Gao (Advances in Civil Engineering)
The rapid development of urban above- and underground transportation has brought an increasing number of deep foundation pit projects that close to existing urban viaducts. Excavation of the deep foundation pit projects leads to soil movement around the pile foundation, which adversely affects the adjacent existing pile foundation and seriously threatens the operation safety of the adjacent existing viaduct. In this paper, the three-dimensional numerical model of foundation pit excavation, viaduct, and pile foundation was established by using the MIDAS GTS against the background of the basement foundation pit project in the new Guangzhou Baiyun Station comprehensive transportation hub building, production, and life complex, where the interaction between foundation pit excavation and viaduct pile foundation was simulated. The influence of various excavation-related factors and different parameters of the pile foundation on lateral displacements of the pile body adjacent to the existing pile foundation was analyzed. The variables controlled in the numerical model included the different excavation depths of the foundation pit, the distance between the excavation surface and the adjacent pile foundation, the spatial effect of different excavation sequences, the diameter of the pile that adjacent to the existing pile foundation, and the elastic modulus of the bored occlusal pile support structure. The results indicated that the lateral displacement of the pile body of the bridge pile foundation was significantly affected by the excavation of the deep foundation pit. The excavation depth exerted the greatest influence on the lateral displacement of the pile foundation, followed by the distance between the pile foundation and the excavation surface, the excavation sequence of the foundation pit, and the elastic modulus and the diameter of the bored occlusive pile support structure. Among them, the pile foundation located at the corner of the foundation pit was negligibly affected by these influencing factors. The findings in this study can provide valuable experiences for similar projects.